Pengaruh Penggunaan Media Pembelajaran Video Fragmen Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 1 Onanrunggu Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Gultom, Mesi; Siagian, Albiner; Samosir, Taripar Aripin (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
This research aims to determine whether the learning motivation of students who are taught with fragment video media is higher than the learning motivation of students who are taught without fragment video media in Class VIII of SMP Negeri 1 Onanrunggu, Samosir Regency. The method used in this research is a quantitative method, a True-Experimental approach with a Posttest-Only Control Design form. The population was all 90 students in class VIII of SMP Negeri 1 Onanrunggu and the sample was determined to be 30 in the experimental class and 30 in the control class using purposive sampling techniques. The results of the analysis show that the average learning motivation of students who were taught using video fragment media (3.518) was higher than the learning motivation of students who were taught without video fragment media (3.345). Data analysis uses the variance pool t test formula, according to the test analysis requirements, namely n1 = n2 and the variance of the two sample groups is homogeneous. The results of data analysis show the value of tcount = 3.991 > ttable (α = 0.01; dk = n1+n2-2 = 58) = 2.392, so H0 is rejected and H1 is accepted. Thus, the researchers concluded that the learning motivation of students who were taught with fragment video media was higher than the learning motivation of students who were taught without fragment video media in class VIII of SMP Negeri 1 Onanrunggu, Samosir Regency, Academic Year 2023/2024.